The best of Comedy Central presents. II [videorecording (DVD)] - Miller, Paul; Attell, Dave; Birbiglia, Mike; Caliendo, Frank, 1974-; Galifianakis, Zach; Lynch, Stephen, 1971-; Oswalt, Patton, 1969-; Swardson, Nick, comedian; Tosh, Daniel (Paramount Home Entertainment, 2008)
The best of Comedy Central presents is back with an all-new array of your favorite comedians, and they're totally uncensored! Watch as they rant about proper concert etiquette, help you discover the true meaning of "time-traveling" and impersonate some of today's biggest stars